Badania nad zachowaniami i preferencjami konsumenckimi w zakresie słodyczy - opinie opolan - Kauf, Sabina (From the Research on the Behaviour and Preferences of Consumers within the Range of Sweets - Opinion of Opole Inhabitants, 2006)
Based on the obtained research results an attempt to present the behaviour of consumers from Opole is undertaken in this article. It concentrates to show the following problems:- sweet consumption versus demographic features of respondents,- influence of a country of origin and a brand on the behaviour of consumers on the market of sweets,- a place of purchase.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 478-485